Moderating effect of culture on the relationship between entrepreneurial competencies, entrepreneurial orientation and women entrepreneurs’ business success in North-Western Nigeria - Hashimu, Salaudeen Nuraini (2018)
The operation of women-owned businesses in Nigeria have been characterised by high rates of failure, despite the supports received from the successive governments. This study draws upon the twin theories of Microfoundations of the Resource-Based View (RBV) and Contingency Theory, to empirically examine the moderating effect of culture on the relationship between entrepreneurial competencies and individual entrepreneurial orientation on the women entrepreneurs’ business success. Using a quantitative approach, data were obtained from a sample of 361 women micro-entrepreneurs through questionnaire survey. Partial Least Squares (PLS-SEM) technique of data analysis was employed to test the hypothesized relationships and findings showed that entrepreneurial competencies have a significant and positive relationship on the women entrepreneurs’ business success, whereas its relationship with culture was found to be negative and significant. However, the relationship between individual entrepreneurial orientation and women entrepreneurs’ success was also not significant. Similarly, culture was found to moderate the relationship between entrepreneurial competencies and women entrepreneur’s success, whereas its interaction with individual entrepreneurial orientation was not supported. The study further illustrates on how the reflective-formative model of higher order construct (HOC) is tested, which is an uncommon practice in the current literature of entrepreneurship. On the whole, the findings reveal the importance of entrepreneurial competencies in achieving women entrepreneurs’ success and suggest on the need to develop the individual entrepreneurial orientation of the women entrepreneurs. Additionally, it stressed on the need to develop the culture of entrepreneurship among the women entrepreneurs through national education policy, training, apprenticeships, and active participation in economic ventures. These findings have no doubt contribute to the mainstream of women entrepreneurship literature by expounding the female conception of success in business, highlighting the importance of human capabilities, and the influence wield by culture on the women entrepreneurs.